Modulação excitatória das células principais do núcleo medial do corpo trapezoide por receptores metabotrópicos glutamatérgicos do Grupo I - Éverton dos Santos e Alhadas (2019)
Metabotropic glutamate receptors (mGluR) are G protein-coupled receptors widely distributed in the central nervous system. In previous work, using intracellular registers, I showed that the activation of mGluR receptors rapidly and reversibly alters the excitability of neurons in the medial nucleus of the trapezoid body (MNTB). Specifically, treatment with the selective agonist, DHPG (100 μM), depolarizes the neurons, increases membrane resistance, reduces reobase, and increases the number of action potentials by a given intensity of injected current. In the present work, we try to evaluate the mechanisms responsible for these effects and the functional consequences for the synapse performance. For this, we performed membrane and membrane current potential records using the patch clamp technique in the whole cell mode. As observed using intracellular registries, using the whole-cell technique DHPG (10-100 μM) depolarized the MNTB neurons by 7.2 ± 1 mV (N = 10). Under voltage clamp (Vm = 60 mV), DHPG generated an input current of -70 ± 8 pA (N = 10), and at the same time increased membrane resistance. The current generated by DHPG was significantly reduced when measured in the presence of MPEP. However, about 60% of the current generated by DHPG was insensitive to MPEP (mGlu5), suggesting the participation of the mGlu1 receptor. Pre-treatment with MPEP and LY367685 (mGlu1) abolished the effect of DHPG (N=4), demonstrating clear agonist action, DHPG, acting on mGluR-I receptors on MNTB neurons. The use of antagonists allowed to discard the participation of iGluRs receptors (NMDA, AMPA and Kainate) and NaV channels in the effect promoted by the activation of Group I metabotropic receptors. To better explore the nature of the current generated by DHPG, we applied voltage clamp protocols in the form of ramps that extended from -120 mV to -30 mV and allowed to measure the current-voltage (IV) relation in this potential range. By the digital subtraction of the curves measured in the presence of DHPG and the curves measured in control, the voltage dependence of the DHPG activated current was calculated. Such analysis revealed a negative current, which tends to zero at potentials near the equilibrium potential of K+. Together, these data suggest that the current generated by DHPG, which manifests itself as an input current, actually occurs by inhibiting an output current through a channel for K+. The present study also indicates that positive current injection mimics the effect of DHPG application leading to the conclusion that the main effect of the activation of mGluR-I receptors on action potentials is mediated by membrane depolarization. To evaluate the functional consequences of the activation of mGluR-I receptor, we stimulated the afferent fiber forming the glutamatergic synapse Calyx of Held and measured the EPSPs and APs generated in the MNTB neuron. Whenstimulated at the rate of 100 Hz (duration of the stimulus 1 s), there was depression of the EPSP size and post-synaptic failures (i.e., generation of EPSPs whose amplitudes were insufficient to generate a PA). Analysis of the results revealed a clear reduction of postsynaptic failures in the presence of DHPG when compared to the control condition, measured in the same cell. This difference was not due to changes in synaptic plasticity because neither facilitation nor depression were significantly altered. The findings suggest that the activation of Group I mGluR increases the chance of EPSPs of the same amplitude triggering post-synaptic action potentials. We conclude that the changes in intrinsic excitability caused by the activation of mGluR-I receptors result in important consequences for the robustness of high-frequency neurotransmission, which is a characteristic of this synapse.